Correlation Coefficient and path Analysis of Eleven Indigenous Potato Varieties in Bangladesh - Biswas, MK; Hossain, M; Islam, R (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Correlation coefficient, path analysis, indigenous, potato (Solanum tuberosum L.) Bangladesh j. genet. biotechnol. 7(1&2): 25-27 2006 (June & December)